Assessment of theMineral Composition of Heaving Soils Using Geotechnical Properties - Fondjo, Armand, Augustin; Theron, Elizabeth (Civil Engineering and Architecture 8(4): 619-631, 2020, 2020)
The behaviour of heaving soils is generally governed by the matric suction. Nonetheless, the mineralogical characteristics influence the geotechnical behaviour. X-ray diffraction is a common technique used to determine the mineral composition. This equipment is costly and the process time-consuming. The objective of this research is to develop predictive mathematical models to determine the predominant minerals in heaving soils. Soil samples are collected from identified areas across Free State province by digging at 50 cm depth from the ground surface. Geotechnical lab studies such as particle size distribution, Atterberg limits, specific gravity, free swell ratio, free swell index, linear shrinkage, and X-ray diffraction are performed to evaluate soil properties. A stepwise analysis is conducted to determine the response of each type of mineral to soil properties, and select the best subsets. Moreover, the influence of soil minerals on soil properties is achieved by investigating the correlation between the relevant soil properties and each mineral. Multivariate regression is performed utilizing MINITAB 18 program to develop mathematical predictive models. These equations are assessed base on correlation coefficient, probability value (P-value), and standard residual pattern analysis. The predominant minerals can be assessed with acceptable accuracy utilizing the proposed semi-empirical models.
Article
Keywords: Soil Mineralogy; Regression Analysis; Geotechnical Properties; X-ray Diffraction